The use of yellow velvetleaf (Limnocharis flava) as a natural color for colet technique using cold wax. Issue 1 (March 2021) - Musdalifah, M; Marfiana, E; Nurmasitah, S
Abstract: Yellow velvetleaf is a fast-growing plant. It cannot be optimally used, particularly the old leaves. Old yellow velvetleaf waste has not been used appropriately, even though it has more benefits and value. The leaves of yellow velvetleaf contain natural color of carotenoids and flavonoids which can be used for natural dyes. The potential color produced can possibly be applied for textile coloring colet technique using cold wax. The research method was carried out through experiments and data analysis using descriptive analysis. The results show that yellow velvetleaf can be used for colet coloring technique using cold wax, and the resulted colors differs depending on the mordant used. Color aging test shows that during the process of nglorod (wax exfoliating) using water, the darkest color was found in tunjung mordant with a color different of 81-100, belongs to "very dark" category. The test of fastness to rubbing shows score of 4 (good) for all samples. The highest result for motif sharpness test is found in the process of nglorod with water and tunjung mordant with color different of 81-100, which is categorized as "very sharp".